UMA HISTÓRIA DOS GRUPOS ESCOLARES DE SÃO LUÍS A PARTIR DAS FINALIDADES DO ENSINO DE DESENHO (1903-1912). - JESUS, Danielle Sousa de (2021)
This research aims to mark the purposes about the subject Drawing in São Luís- MA School Groups, during the period between 1903 and 1912.The initial time frame was delimited by the authorization of School Groups creation in this state, starting through Maranhão city in 1903.The final time frame is situated in 1912, year that we analyze an absence of these groups in Maranhão City. In this context, it raises the question of this research. What are the purposes of teaching Drawing in São Luís School Groups (1903-1912)? In this way, researching about the goals of Drawing on School Groups seeking to understand school practices and how the conceptions and pedagogical instruments were officially designed and thought on official documents is essential for the history writing of mathmatics education in Maranhão City. Thus, in order to understand which goals were related to the subject Drawing in São Luís School Groups and how they featured themselves, official documents were located and examineted and they were set up in the Ordinances, Regiments, Eduacational Programs, Reports, Messages, Laws, Decrees, apart from Magazines and Newspapers. This study was developed through a historical perspective from a documentary analysis using cultural history studies, considering the Works from Roger Chartier (2002), Dominique Julia (2001) and the history of school subjects by André Chervel (1990), beyond the ideas from Valente (2007, 2008, 2010, 2013), Silva (2011, 2017) and Guimarães (2017) about the history of math education, Maranhão School Groups and Drawing on Elementary School, respectively. The examined sources took place in Maranhão Public Archive, Benedito Leite Public Library, Maranhão Historic and Artistic Institute (IPHAN) Josué Montello Cultural House, Assis Chateaubrian Library,Ferreira Gullar Library, Historic and Geographical Institute of Maranhão, Rosa Castro Library, Astolfo Marques Library, in the School Inspection of State Department Education, in the School Inspection of Municipal Department Education and digital library holdings from the National Library and Benedito Leite Public Library. As conclusion, the Drawing teaching was a present element in the educational culture on School Groups and it had as a purpose developing observation, perception, children´s creativity, the practice of educating the eye and the hand and help other subjects in the primary school on school groups, acting as an improving instrument of representations and language comprehension. The methodological indications based on this knowledge were associated with the intuitive teaching method. About the contents, they were given gradually, taught successively and in progression by difficult degrees for each year.